2019
DOI: 10.1002/hep.30830
|View full text |Cite
|
Sign up to set email alerts
|

Ledipasvir‐Sofosbuvir for 12 Weeks in Children 3 to <6 Years Old With Chronic Hepatitis C

Abstract: For children under 12 years of age who have chronic hepatitis C virus (HCV) infection, there are currently no approved treatments with direct‐acting antiviral agents. We therefore evaluated the safety and efficacy of ledipasvir‐sofosbuvir in HCV‐infected children aged 3 to <6 years. In an open‐label study, patients 3 to <6 years old chronically infected with HCV genotype 1 (n = 33) or 4 (n = 1) received weight‐based doses of combined ledipasvir‐sofosbuvir as granules (33.75 mg/150 mg for weights <17 kg or 45 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 31 publications
(56 reference statements)
5
80
0
2
Order By: Relevance
“…Three clinical trials supporting the approval of ledipasvir/sofosbuvir in the pediatric population aged ≥ 3 years demonstrated high SVR12 rates comparable to those observed in adults. (281)(282)(283) Limited real-world data further corroborate these findings. (284,285) In September 2019, the FDA approved weightbased sofosbuvir plus ribavirin for treatment-naive and interferon-experienced (± ribavirin) children aged ≥ 3 years with genotype 2 or 3, without cirrhosis or with compensated cirrhosis (Child-Pugh A).…”
Section: An 8-week Course Of the Daily F Ixed-dose Combination Of Glementioning
confidence: 60%
See 1 more Smart Citation
“…Three clinical trials supporting the approval of ledipasvir/sofosbuvir in the pediatric population aged ≥ 3 years demonstrated high SVR12 rates comparable to those observed in adults. (281)(282)(283) Limited real-world data further corroborate these findings. (284,285) In September 2019, the FDA approved weightbased sofosbuvir plus ribavirin for treatment-naive and interferon-experienced (± ribavirin) children aged ≥ 3 years with genotype 2 or 3, without cirrhosis or with compensated cirrhosis (Child-Pugh A).…”
Section: An 8-week Course Of the Daily F Ixed-dose Combination Of Glementioning
confidence: 60%
“…A 12‐week course is recommended for patients without cirrhosis; 24 weeks is recommended for those with compensated cirrhosis. Three clinical trials supporting the approval of ledipasvir/sofosbuvir in the pediatric population aged ≥ 3 years demonstrated high SVR12 rates comparable to those observed in adults . Limited real‐world data further corroborate these findings …”
Section: Hcv In the Pediatric Populationmentioning
confidence: 96%
“…40,81,82 A large phase II and III, open-label, multicenter, multicohort study evaluated the safety and the efficacy of sofosbuvir (a potent NS5B polymerase inhibitor) and ledipasvir (an NS5A inhibitor). [83][84][85]…”
Section: Sofosbuvir/ledipasvirmentioning
confidence: 99%
“…Results of the same association are available for children aged 6 to 11 years 83 and for those aged 3 to 5 years (►Table 3). 84 Treatment duration was 12 weeks for all except one patient with HCV genotype 1 infection who was treatment-experienced and cirrhotic and two patients with HCV genotype 3 infection who received 24 weeks of therapy. 2 The pharmacokinetic analyses showed that the "half strength" dosing resulted in plasma concentration generally within the range of those observed in adults.…”
Section: Children Younger Than 12 Yearsmentioning
confidence: 99%
“…Paediatric trials of several combinations of all oral therapy have been published (Table ) . Some of these regimens have been licenced by the US Food and Drug Administration (FDA) and European Medicines Agency in 2017 for children older than 12 years.…”
Section: Hepatitis Cmentioning
confidence: 99%